Risk of Surgical Site Infection (SSI) following Colorectal Resection Is Higher in Patients With Disseminated Cancer: An NCCN Member Cohort Study. (19th March 2018) - Kamboj, Mini; Childers, Teresa; Sugalski, Jessica; Antonelli, Donna; Bingener-Casey, Juliane; Cannon, Jamie; Cluff, Karie; Davis, Kimberly A.; Dellinger, E. Patchen; Dowdy, Sean C.; Duncan, Kim; Fedderson, Julie; et al.
Abstract : BACKGROUND: Surgical site infections (SSIs) following colorectal surgery (CRS) are among the most common healthcare-associated infections (HAIs). Reduction in colorectal SSI rates is an important goal for surgical quality improvement. OBJECTIVE: To examine rates of SSI in patients with and without cancer and to identify potential predictors of SSI risk following CRS DESIGN: American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) data files for 2011–2013 from a sample of 12 National Comprehensive Cancer Network (NCCN) member institutions were combined. Pooled SSI rates for colorectal procedures were calculated and risk was evaluated. The independent importance of potential risk factors was assessed using logistic regression. SETTING: Multicenter study PARTICIPANTS: Of 22 invited NCCN centers, 11 participated (50%). Colorectal procedures were selected by principal procedure current procedural technology (CPT) code. Cancer was defined by International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) codes. MAIN OUTCOME: The primary outcome of interest was 30-day SSI rate. RESULTS: A total of 652 SSIs (11.06%) were reported among 5, 893 CRSs. Risk of SSI was similar for patients with and without cancer. Among CRS patients with underlying cancer, disseminated cancer (SSI rate, 17.5%; odds ratio [OR], 1.66; 95% confidence interval [CI], 1.23–2.26; P =.001), ASA score ≥3 (OR, 1.41; 95% CI, 1.09–1.83; P =.001), chronic obstructive pulmonary disease (COPD; OR, 1.6; 95% CI, 1.06–2.53; P =.02), and longer duration of procedure were associated with development of SSI. CONCLUSIONS: Patients with disseminated cancer are at a higher risk for developing SSI. ASA score >3, COPD, and longer duration of surgery predict SSI risk. Disseminated cancer should be further evaluated by the Centers for Disease Control and Prevention (CDC) in generating risk-adjusted outcomes. Infect Control Hosp Epidemiol 2018;39:555–562